2017
DOI: 10.3390/rs9010079
|View full text |Cite
|
Sign up to set email alerts
|

Near Real-Time Browsable Landsat-8 Imagery

Abstract: Abstract:The successful launch and operation of Landsat-8 extends the remarkable 40-year acquisition of space-based land remote-sensing data. To respond quickly to emergency needs, real-time data are directly downlinked to 17 ground stations across the world on a routine basis. With a size of approximately 1 Gb per scene, however, the standard level-1 product provided by these stations is not able to serve the general public. Users would like to browse the most up-to-date and historical images of their regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Similar to the discussion on the Sentinel Explorer, cirrocumulus clouds and haze limit the dynamic range of contrast and deteriorate the quality of the visual effect. The right panels are pansharpened using a spectral summation intensity modulation technique [26] and then LOD-based enhancement (Equation ( 1)) with a linear transition (Equation ( 2)). As a result, the improvements in the visual effect and the spatial details are apparent when comparing the right panels to the middle and left panels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the discussion on the Sentinel Explorer, cirrocumulus clouds and haze limit the dynamic range of contrast and deteriorate the quality of the visual effect. The right panels are pansharpened using a spectral summation intensity modulation technique [26] and then LOD-based enhancement (Equation ( 1)) with a linear transition (Equation ( 2)). As a result, the improvements in the visual effect and the spatial details are apparent when comparing the right panels to the middle and left panels.…”
Section: Resultsmentioning
confidence: 99%
“…Unless it can be masked out completely, a small patch of cloud or haze will render the LCE approach invalid. As demonstrated by Liu et al [26], this problem can be tackled by masking out clouds and applying the adaptive contrast enhancement (ACE) technique [27] to those regions without cloud masking, and then adding back the cloud mask with a saturated value. The ACE technique assigns each pixel to an intensity proportional to its rank within the surrounding neighborhood.…”
Section: Preliminaries and The Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that CloudNet improved the accuracy of predictions without causing performance degradation and other costs. CloudNet will be incorporated into the Open Access Satellite Image Service (OASIS, http://oasis.ncku.edu.tw) [31] to support the calculation of near real-time changes in LULC over the Taiwan area in a fully automated fashion. A total of 5,017,600 pixels (manually labeled Sentinel-2 clouds) were created for training and validation in this study, and we released the manually labeled cirrus-sufficient dataset so that researchers in related fields can effectively apply it to their own research.…”
Section: Discussionmentioning
confidence: 99%
“…CFMask is made available by the Earth Resources Observation and Science Center of the U.S. Geological Survey (USGS) in order to provide standard Landsat Level-1 data products, including cloud, cloud confidence, cloud shadow, and snow/ice masks. It has been incorporated into the L-8 Automatic Image Processing System to process all scenes of Landsat-8 imagery covering the Taiwan area on an operational basis [31]. However, CFMask has difficulties over bright targets, and thin clouds or haze are usually omitted.…”
Section: Training Datasetmentioning
confidence: 99%